Analisis Tindak Perundungan Siswa Sekolah Dasar dan Upaya Penanggulangannya - Mohamad Noor Fajar Al Arif Fitriana; Ahmad Fauzi (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2023)
Ensuring a solid foundation through basic education is crucial for students progressing to higher levels. In the learning process, creating a conducive environment is essential for comfort and effectiveness. However, a prevalent hindrance to this is bullying, particularly among elementary school students. In Indonesia, numerous bullying cases involving students have been reported, significantly impacting the learning atmosphere. Bullying manifests as a psychosocial problem where individuals repeatedly insult and humiliate others, exerting power over victims. This aggressive behavior can be physical or verbal, marked by a power imbalance between perpetrator and victim. Empathy plays a pivotal role in mitigating bullying, as individuals understanding and caring about the victim's feelings are less prone to engaging in violent acts. Educational practitioners can address bullying's impact through intervention programs, engaging parents, peers, educators, counselors, administrators, and the broader school community. Collective participation is essential, with everyone in the school community contributing to counteracting bullying. The legal framework provided by Permendikbud No. 82/2015 serves as a comprehensive guide for anti-bullying measures in schools. It delineates the responsibilities of various stakeholders and offers a structured approach to address and prevent bullying incidents. Ultimately, fostering a culture of empathy and collective responsibility is vital for creating safe and nurturing learning environments at all levels of education.